2D Materials: Lattice Structure and Bandgap Control of 2D GaN Grown on Graphene/Si Heterostructures (Small 14/2019). Issue 14 (5th April 2019) - Wang, Wenliang; Li, Yuan; Zheng, Yulin; Li, Xiaochan; Huang, Liegen; Li, Guoqiang
Abstract : In article number1802995, Guoqiang Li and co‐workers demonstrate a 2D GaN with wellcontrolled lattice structure and bandgap on graphene/Si hetero‐structure. The bandgap for 2D GaN in P63 MC and R3m structure is determined to be ≈4.65 and ≈4.18 eV, respectively. The 2D GaN shows a great potential for the development of deep ultraviolet devices.